Peningkatan Hasil Belajar Matematika Menghitung Volume dan Luas Permukaan Bangun Ruang melalui Media Bangun Ruang Pada Siswa Kelas V MI YPSM Mangiran - Fatimah, Siti; Nurhayati, Rosidah (Primera Educatia Mandalika: Elementary Education Journal, 2025)
This study aims to improve the mathematics learning outcomes of fifth grade students of MI YPSM on the material of calculating the volume and surface area of ​​solid shapes using concrete solid shapes media. This study uses a Classroom Action Research (CAR) approach with two action cycles, each consisting of planning, implementation, observation, and reflection. The objects of the study were 25 fourth grade students of MI YPSM Mangiran, Kediri Regency in the 2017/2018 Academic Year. In cycle I, the application of solid shape media in the form of three-dimensional models such as cubes, blocks, prisms, and pyramids, succeeded in increasing the class average score from 62 in the pre-action to 71, with the percentage of students who completed reaching 64%. In cycle II, with improvements to the method and more time given to practice using concrete media, the class average score increased to 78 and 22 students (88%) succeeded in achieving the Minimum Completion Criteria (KKM) that had been set. The results showed that the use of solid shape media was effective in improving students' understanding of the concept of volume and surface area of ​​solid shapes.